KARAKTERISTIK GENERASI Z DAN KESIAPANNYA DALAM MENGHADAPI BONUS DEMOGRAFI 2030 DI PROVINSI SUMATERA UTARA - Claudya Carolin Sihombing; Elsa Kardiana; Dinda Aprilia; Lajuardi Putra Beheng Sinulingga; Elno Situmorang; Lastri Marbun (STKIP Subang, 2025)
This study aims to comprehensively analyze the characteristics of Generation Z and measure their level of preparedness to face the peak of the Demographic Bonus in 2030 in North Sumatra Province. The demographic bonus phenomenon offers massive economic acceleration opportunities for Indonesia, but its success depends heavily on whether the productive-age population has adequate quality, competence, and mental readiness. This study employed a mixed-methods design that integrates quantitative and qualitative data. Primary data was collected through an online questionnaire distributed to 50 randomly selected Generation Z respondents, while secondary data was obtained through an in-depth literature study. The results indicate that Generation Z in North Sumatra has a relatively high readiness profile and an optimistic attitude towards the future. Their fundamental strengths lie in superior digital capabilities (92% of respondents demonstrated good digital literacy in verifying information), strong learning independence (Do It Yourself), a realistic, solution-oriented mindset, and a very high level of social and multicultural openness (96%). However, this study also highlighted structural challenges in the aspects of discipline and time management (44% of respondents admitted to being ineffective) and low geographic awareness of local economic potential (32%). The study's conclusion confirms that although Generation Z possesses substantial intellectual and social capital as drivers of development, this potential remains underutilized due to barriers to personal productivity and a lack of connectivity to regional opportunities. Strategic interventions focused on improving managerial soft skills and educating about regional economic potential are needed.